2012
DOI: 10.1093/hmg/dds140
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase ARFRP1 controls the lipidation of chylomicrons in the Golgi of the intestinal epithelium

Abstract: The uptake and processing of dietary lipids by the small intestine is a multistep process that involves several steps including vesicular and protein transport. The GTPase ADP-ribosylation factor-related protein 1 (ARFRP1) controls the ARF-like 1 (ARL1)-mediated Golgi recruitment of GRIP domain proteins which in turn bind several Rab-GTPases. Here, we describe the essential role of ARFRP1 and its interaction with Rab2 in the assembly and lipidation of chylomicrons in the intestinal epithelium. Mice lacking Arf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…In a recent study, we showed that chylomicron formation, lipidation as well as apolipoprotein assembly, is dependent on the trans -Golgi and ARFRP1 ( 13 ). ARFRP1 is required for the correct recruitment and action of other GTPases (ARL1 and Rab proteins) that interact with the scaffolding protein golgin-245.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, we showed that chylomicron formation, lipidation as well as apolipoprotein assembly, is dependent on the trans -Golgi and ARFRP1 ( 13 ). ARFRP1 is required for the correct recruitment and action of other GTPases (ARL1 and Rab proteins) that interact with the scaffolding protein golgin-245.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished lipid droplet fusion and elevated lipolysis were responsible for smaller lipid droplets in brown adipose tissue ( 12 ). Furthermore, in a recent study it was shown that in the intestine ARFRP1 is involved in the formation and lipidation of lipid-carrying chylomicrons ( 13 ). Besides its fundamental role in whole body glucose homeostasis, the liver is further essential for the distribution of lipids in the body via synthesis and secretion of VLDLs.…”
Section: Detection Of Apob48/100 Synthesis and Clearance By Pulse-chamentioning
confidence: 99%
See 2 more Smart Citations
“…1) (Chang et al, 2015;Cruz-Garcia et al, 2013;Eiseler et al, 2016;Gehart et al, 2012;Hesse et al, 2013;Hsu et al, 2016;Labbaoui et al, 2017;Lieu et al, 2008;Liu et al, 2006;Lock et al, 2005;Marešová and Sychrová, 2010;Marešová et al, 2012;Murray and Stow, 2014;Price et al, 2005;Torres et al, 2014;Yang and Rosenwald, 2016). In mammalian cells, these functions affect a wide range of fundamental cellular processes, including cell polarity (Lock et al, 2005), innate immunity (Bremond et al, 2009;Lieu et al, 2008;Murray and Stow, 2014;Stanley et al, 2012), lipid droplet and chylomicron formation (Hesse et al, 2013;Jaschke et al, 2012), as well as the secretion of insulin (Gehart et al, 2012), chromogranin A (CruzGarcia et al, 2013) and matrix metalloproteinases (MMPs) (Eiseler et al, 2016). In yeast, Arl1 and its effectors are also involved in numerous functions, such as maintenance of cell wall integrity (Liu et al, 2006), ion homeostasis (Marešová and Sychrová, 2010;Munson et al, 2004;Rosenwald et al, 2002), tolerance to stress factors (Jaime et al, 2012;Marešova et al, 2012;Yang and Rosenwald, 2016), regulation of cell proliferation (Benjamin et al, 2011), the unfolded protein response (UPR) (Hsu et al, 2016) and also in the ability of yeast to cause disease (Labbaoui et al, 2017).…”
Section: The Physiological Roles Of Arl1mentioning
confidence: 99%